Existential and Sociological Interpretations of the Concepts “Situation” and “Context” - Мельніков, Андрій Сергійович; Мельніков, А. С.; Мельников, Андрей Сергеевич; Melnikov, Andrii S.; Melnikov, Andrey; Johnson, John M. (Italy : Franco Angeli, 2018)
Existential thought is a broad and ambiguous intellectual and cultural movement which developed in Western Europe in the first half of the XX century. Existential thinkers, and those influenced by existentialism in different areas of arts and sciences, emphasize the individual’s struggle to find or create meaning, and implied that the meaning of a human act is related to the immediate cultural, social, and historical context or situation. The emergence of “situational ethics” was one development influenced by existential ideas. This paper analyzes these ideas about “context” or “situation,” first by some existential progenitors, and then by social scientists who have sought to integrate core existential ideas or themes into contemporary social science; symbolic interactionism, dramaturgical sociology, ethnomethodology, grounded theory, and existential sociology.

Экзистенциальная мысль - это широкое и неоднозначное интеллектуальное и культурное движение, развившееся в Западной Европе в первой половине XX века. Экзистенциальные мыслители и те, кто находился под влиянием экзистенциализма в различных областях искусств и наук, подчеркивают что борьба человека за поиск или создание смысла и подразумевала, что значение человеческого действия связано с непосредственным культурным, социальным и историческим контекстом или ситуацией. Возникновение «ситуационной этики» было одним из событий, на которое повлияли экзистенциальные идеи. В данной статье анализируются эти идеи о «контексте» или «ситуации» сначала некоторыми экзистенциальными прародителями, а затем социологами, которые стремились интегрировать основные экзистенциальные идеи или темы в современнуюй социальную науку; символический интеракционизм, драматургическая социология, этнометодология, обоснованная теория и экзистенциальная социология.

Екзистенційна думка - це широкий і неоднозначний інтелектуальний і культурний рух, який розвинувся в Західній Європі в першій половині XX століття. Екзистенційні мислителі та ті, хто зазнав впливу екзистенціалізму в різних областях мистецтв і наук, наголошують на боротьбі людини за пошук або створення сенсу, і мається на увазі, що значення людського вчинку пов’язане з безпосереднім культурним, соціальним та історичним контекстом чи ситуацією. Виникнення «ситуативної етики» було одним із подій, на які вплинули екзистенційні ідеї. У цій роботі аналізуються ці уявлення про "контекст" або "ситуацію" спочатку деякими екзистенційними родоначальниками, а потім соціальними вченими, які прагнули інтегрувати основні екзистенційні ідеї або теми в сучасну соціальну науку; символічний інтеракціонізм, драматургічна соціологія, етнометодологія, обґрунтована теорія та екзистенціальна соціологія.
Melnikov А. Existential and Sociological Interpretations of the Concepts “Situation” and “Context” : [розділ монографії] / А. Melnikov, J. M. Johnson // The present and future of symbolic interaction, Vol. II / D. Altheide, C. Nuti, A. Salvini, eds. - Italy : Franco Angeli. - 2018. - Р. 15-28.